2012
DOI: 10.1038/aja.2011.178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-acting testosterone undecanoate treatment on quality of life in men with testosterone deficiency syndrome: a double blind randomized controlled trial

Abstract: This study aimed to investigate the effect of intramuscular injection of testosterone undecanoate on overall quality of life (QoL) in men with testosterone deficiency syndrome (TDS). A randomized controlled trial over a 12-month period was carried out in 2009. One hundred and twenty men aged 40 years and above with a diagnosis of TDS (serum total testosterone ,12 nmol l 21 and total Aging Male Symptom (AMS) scores o27) were invited to participate. Interventions comprised intramuscular injection of either place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…TU significantly increased serum TT level in aging Malaysian men and was safe and well tolerated. Results on the effect of TU using the Aging Male Symptoms score and on quality of life in the present study have been reported previously . The present study is one of the few double‐blind placebo‐controlled trials involving Asian men.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…TU significantly increased serum TT level in aging Malaysian men and was safe and well tolerated. Results on the effect of TU using the Aging Male Symptoms score and on quality of life in the present study have been reported previously . The present study is one of the few double‐blind placebo‐controlled trials involving Asian men.…”
Section: Discussionsupporting
confidence: 79%
“…This study was part of a bigger randomised placebo-controlled trial. The efficacy of TU in improving symptoms of TD has been reported previously [18].…”
Section: Introductionmentioning
confidence: 87%
“…Additionally, Tong et al. evaluated the influence of a long‐acting testosterone formulation in hypogonadal men QOL and observed a significant improvement in mental health after 30 weeks of treatment (Tong, Ng, Lee, & Lee, ). Although the QOL findings presented in Table do not allow the establishment of a link between TRT and QOL, which involves a range of interfering factors, they agree with Tong and collaborators' conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Established benefits of T therapy in hypogonadal men include improved sexual desire and function, [12][13][14][15] improved energy, mood, and vitality, [15][16][17][18][19] increased lean mass, 14,[19][20][21][22] decreased waist circumference, [23][24][25][26][27] reduced total body fat mass, [19][20][21][22] and increased bone mineral density. [28][29][30][31] Promising new data reveal that T therapy improves insulin sensitivity [32][33][34] and reduces blood glucose 23,25,35 and hemoglobin A 1c (HbA 1c ) 23,25,27,35 levels in men with type 2 diabetes or obesity.…”
Section: Introductionmentioning
confidence: 97%